Physical activity on prescription in Swedish primary care: a survey on use, views, and implementation determinants amongst general practitioners - Elina Brorsson Lundqvist; Marcus Praetorius Björk; Susanne Bernhardsson (Taylor & Francis Group, 2024)
AbstractIntroduction Swedish Physical Activity on Prescription (PAP) has been shown to increase physical activity levels, which is known to lead to positive health effects. PAP is being implemented in Swedish healthcare to various extents. However, there is a lack of knowledge about how Swedish general practitioners (GPs) work with PAP and what hinders and facilitates wider implementation.Aims This study aimed to survey GPs' use and views of PAP, identify barriers and facilitators for implementing PAP, and explore associations to gender, practice location, and experience.Methods The study was framed by the Normalization Process Theory. A survey was sent to 463 GPs at 69 different healthcare centres in Region Västra Götaland. Data were analysed using multiple logistic and linear regressions.Results A total of 143 GPs completed the survey (response rate 31%). Views on PAP were generally positive amongst respondents, but only 27% reported using PAP regularly. The most prominent reported barriers were insufficient training and resources. Positive views and willingness to collaborate in using PAP were identified as facilitators. Responding GPs in Gothenburg used PAP more often (OR 6.4; 95% CI 2.7-14.8) and were significantly more positive to the method than GPs in other areas of the region. GPs with more than 10 years of practice used PAP more often (OR 2.5; 95% CI 1.1-6.0) than less experienced GPs. Few of the investigated variables were associated with gender.Conclusions The positive views amongst responding GPs are helpful, but more education, training and resources are needed for successful implementation of PAP in Swedish primary health care.